Systematic Literature Review (SLR): Utilization of Models in Reading Literacy Learning in Elementary Schools - Singgih, Muhammad; Sintha Sih Dewanti; Ibrahim (Elementary Teacher Education Program, Majalengka University, 2025)
This research is based on the literacy crisis experienced by elementary schools in Indonesia, so that the use of learning models is one of the alternatives for educators and researchers in Indonesia to improve the literacy skills of elementary school students. The purpose of this study is to examine the use of appropriate learning models in literacy learning in schools so that it can prove that the use of learning models increases or does not increase students' literacy skills in elementary schools. Systematic literature review is the right research method in reviewing previous research. The articles that have been collected are 8 articles indexed by SINTA using the publish or perish application with the range of 2020-2025. Based on the results of the research of 8 articles studied, students' literacy ability shows that it is still relatively low, so that with the application of the model as one of the steps to improve students' literacy skills, this SLR research has never been conducted to examine more deeply the use of models in literacy learning from each research. The use of appropriate learning models such as Discovery Learning, Talking Stick, PBL, TaRL, Cooperative Integrated Reading and Composition, Buddy Reading, Project-Based Constructivist and VCT has been proven to improve the literacy skills of elementary school students. It can be concluded that the consistent application of various learning models shows a significant improvement in the literacy abilities of elementary school students.